Understanding educational development in terms of the collective creation of socially-just curricula. Issue 8 (17th November 2022) - Ashwin, Paul
ABSTRACT: Suellen Shay's research focused extensively on both the challenges of creating socially-just higher education curricula and the knowledge and practices of the field of educational development. Shay's work highlights the important ways in which curricula define what it means to be educated and the importance of socially-just curricula that provide all students with the opportunity to participate in and succeed through higher education. In order to meet the challenging agenda this creates for curriculum transformation, there is a need to rethink the focus of educational development in higher education. I argue that an important implication of Shay's work is to shift educational development from a focus on the development of individual teachers to focus on the collective creation of socially-just curricula. I explore the implications of this change for understanding the practices and priorities of educational development in higher education.